Preparation of isolated guard cells, containing cell walls, from Vicia faba. - Sara K Fleetwood; Maya Kleiman; E Johan Foster (PLoS ONE, 2024)
Stomatal movement, initiated by specialized epidermal cells known as guard cells (GCs), plays a pivotal role in plant gas exchange and water use efficiency. Despite protocols existing for isolating GCs through proplasting for carrying out biochemical, physiological, and molecular studies, protocals for isolating GCs with their cell walls still intact have been lacking in the literature. In this paper, we introduce a method for the isolation of complete GCs from Vicia faba and show their membrane to remain impermeable through propidium iodide staining. This methodology enables further in-depth analyses into the cell wall composition of GCs, facilitating our understanding of structure-function relationship governing reversible actuation within cells.